Media Di Era Budaya Massa : Tegangan Antara Berkah Dan Bencana Bagi Humaniora - Kasiyan Kasiyan (Ornamen, 2006)
Study of media culture progressively find its significances for society, when this world enter a era named ‘third wave revolution’- technological revolution of communications and information.In this era, media really have come to what term by Mcluhan as the extensions of man which alter this broadness of universe become do not more than global form of village, pressed, even is easy to folded. The problem is emerging when cultural text of media in the reality is chained very tight with the dark side of advanced capitalism ideology, what frequently call just for the benefit of economic advantage nothing other than, and have to sacrifice the dimension of human values. Here finally, media stays in its ambiguous dilemma, In one side, it has potency as benediction, but other beside, often tend to more having a meaning as disaster. Nearer meaning of media phenomenon as disaster caused such as establishing of destructive ideology carried in its existences. Other which is dominant,is establishing ideology: image and manipulation, dehumanization,and necrophilia. Therefore, pursuant to some critical points - and also due to the reality and magnitude of significance of the meaning of media culture in this era - hence more commitment to the cultural study of media becoming very insist on and important to be conducted, for the possibility to take apart of discourse of outlet revitalization of media that more align to values of human.Keyword: media culture, human value